Kontestasi Teologi Inklusif Pluralisme Agama: Studi Kritis atas Pemikiran Para Tokoh dan Relevansinya di Era Modern - Muhammad Rifky Akbar Sahrul; Muhammad Amri; Andi Aderus (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2026)
This study aims to analyze the concepts of inclusive theology and religious pluralism through a critical examination of the perspectives of religious thinkers from both Islamic theological traditions and modern-contemporary thought. The research employs a qualitative method with a library research approach, using descriptive-critical analysis of the ideas of John Hick, Karl Rahner, Nurcholish Madjid, Abdurrahman Wahid, M. Quraish Shihab, as well as critiques from scholars who reject theological pluralism. The findings reveal that inclusive theology seeks to foster an open, tolerant, and dialogical religious attitude while maintaining the internal theological commitments of each faith tradition. Religious pluralism, meanwhile, encompasses a broad spectrum of meanings, ranging from the recognition of socio-religious diversity to theological perspectives concerning salvation and religious truth. The study further finds that the tension between exclusivism, inclusivism, and pluralism is shaped not only by doctrinal issues but also by historical, social, and hermeneutical factors. It concludes that inclusive theology can serve as an ethical and dialogical foundation for harmonious multicultural life, while religious pluralism should be understood critically and proportionally in order to avoid the extremes of both relativism and absolutism.